Life Satisfaction and Academic Performance of Elementary School Students - Achkar,Ana Maria Nunes El (2019)
Abstract The study aimed to investigate the association of risk and protection factors in the academic performance and life satisfaction of elementary school students. Participants included 400 students of both sexes, aged between 11 and 17 years, and 26 female teachers from public and private schools in the state of Rio de Janeiro. The instruments were: Social Skills Inventory for Adolescents, Social Support Perception Scale, Brazilian Youth Questionnaire and Maslach Burnout Inventory. Main results showed that exposure to family violence by the students, emotional exhaustion and low professional achievement by the teachers contribute to a poor performance of students in school. Students with indicators of social support by the family and the community and of self-control skills presented higher life satisfaction. This study reveals contextual and personal variables that affect students’ socio-emotional and academic development which prove subsidies for future interventions.